Corrosion Inhibition Studies of Mild Steel in Acid Medium Using Chloroquine Phosphate - Subhashini, S.; Rajalakshmi, R. (Asian Journal of Chemistry, 2010)
In this investigation, attempts have been made to study the inhibitive effect of chloroquine phosphate for mild steel in 1 M HCl in the concentration range of 5 × 10-6 M to 1 × 10-2 M by weight loss, DC polarization methods and AC impedance spectroscopy. Results indicate that the addition of chloroquine phosphate to the acid reduce the rate of metal attack. Inhibition efficiency increases with the concentration of chloroquine phosphate. Thermodynamic parameters have also been evaluated. Surface coverage values have been tested graphically for suitable adsorption isotherm. Chloroquine phosphate yielded a maximum of 98.69 % in 1 M HCl, electro chemical studies are carried out with the various concentrations of chloroquine phosphate to find out the nature of the action of chloroquine phosphate. From these results, chloroquine phosphate is found to behave as a mixed type inhibitor.